Terrorist murder, cycles of violence, and terrorist attacks in New York City during the last two centuries - Gomez-Sorzano, Gustavo
: I apply the Beveridge-Nelson business cycle decomposition method to the time series of murder of New York City – NYC (1797-2005). Separating out “permanent” from “cyclical” murder, I hypothesize that the cyclical part coincides with documented waves of organized crime, internal tensions, breakdowns in social order, crime legislation, social, and political unrest, and recently with the periodic terrorist attacks in the city. The estimated cyclical terrorist murder component warns that terrorist attacks in New York City from 1826 to 2005, historically occur in the estimated turning point dates, of whether a declining, or ascending cycle, and so, it must be used in future research to construct a model for explaining the causal reasons for its movement across time, and for forecasting terrorist murder and attacks for New York City.Model of cyclical terrorist murder for Colombia; 1950-2004. Forecasts 2005-2019; the econometrics of violence; terrorism; and scenarios for peace in Colombia from 1950 to 2019; scenarios for sustainable peace in Colombia by year 2019; decomposing violence: crime cycles in the twentieth in the United States; using the Beveridge and Nelson decomposition of economic time series for pointing out the occurrence of terrorist attacks; decomposing violence: terrorist murder; and attacks in New York State from 1933 to 2005